Reassessing the Political Economy of Growth in ASEAN: The Interplay of Political Stability, Government Effectiveness, and Inflation - Maulida, Syahdatul (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
This study aims to analyze the interplay of political stability, government effectiveness, and inflation on economic growth in ten ASEAN countries during the 2019-2023 period. The research employs a quantitative approach using panel data regression analysis based on secondary data from the World Governance Indicators (WGI) and the World Development Indicators (WDI). The findings reveal that political stability has a negative and significant effect on economic growth, whereas government effectiveness exerts a positive and significant influence. Inflation shows a negative but insignificant effect, indicating that price stability in the region remains relatively well-maintained. Collectively, the three variables explain 57.7% of the variation in economic growth, underscoring the importance of institutional factors in driving economic performance. The results suggest that government effectiveness serves as the main channel through which political stability affects economic growth. Policy implications highlight the need for bureaucratic reforms, improvement in public governance quality, and regional cooperation to strengthen institutional capacity within ASEAN. This study contributes to the political economy of development literature by emphasizing the interaction between political and institutional factors in influencing regional economic growth.   Keywords: Political Stability, Government Effectiveness, Inflation, Economic Growth, ASEAN. JEL: E02, O43, O53, P16.